LANGUAGE ACQUISITION OF CHILDREN UNDER 3 YEARS OLD - Shoufi Nisma Dewi (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This study focuses on analyzing language acquasition on children under 3 years old involed by means of descriptive qualitative method. The subject of this research is the children at the age 2 years old named Yuni who lived in Padangsidimpuan. For this research, the writer uses the video recorder to record the conversation of child and parents. In this research, to collect the data the writer applies observation method and video recording of conversation between child and parent. In analyzing the data, the writer conducts some procedures. The data are collected from video recording of the conversation between child and parent. The writer transcribes the recording data and analyzes it based on phonetic of phonem acquisition. Then includes them in approaching language acquisition. The results of the research Phonological errors, Incorrect utterances, Imitation, Correction, Laziness.